2013
DOI: 10.4103/2229-5178.120644
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophic epidermolysis bullosa associated with non-syndromic hypodontia

Abstract: Epidermolysis bullosa (EB) is a genetic disease associated with fragility and bullous lesions of the skin and mucous membranes. There are various patterns of inheritance and histopathology. The disease is associated with systemic and oral manifestations, among which may be dental decay necessitating oral rehabilitation. The aim of this article is to present the course of the condition in a child with dystrophic EB and also to report an association between EB, hypodontia, and supernumerary teeth which has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…EB is a group of rare genetic disorders that involve the blister formation following mild trauma (4). The disease is associated with conspicuous clinical and oral manifestations, which include oral tissue fragility and blistering of the skin and mucosa (4,9,15). Blisters that occur in the oral mucosa heal with scar formation usually start to appear at birth or during the course of the first year of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EB is a group of rare genetic disorders that involve the blister formation following mild trauma (4). The disease is associated with conspicuous clinical and oral manifestations, which include oral tissue fragility and blistering of the skin and mucosa (4,9,15). Blisters that occur in the oral mucosa heal with scar formation usually start to appear at birth or during the course of the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is a chronic mechanobullous disease related to the specific abnormal or absent proteins (2,3). EB was first described by Von Hebra in 1870 and the estimated frequency is 1 of 50,000 births (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Generalized enamel hypoplasia has been reported in 59 case reports of individuals with JEB, 2,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] as well as 100% of the patients with JEB in a series of cases (n = 6 severe JEB-H, n = 19 other types of JEB) (Images 2.3 and 2.4). 46 Enamel hypoplasia can be observed in panoramic radiographs as teeth with thin, abnormal, severely dystrophic enamel formation (Image 2.5). 25 Some authors suggested that generalized enamel hypoplasia in EB is pathognomonic for JEB, and therefore, the teeth phenotype can be used as a guide to the EB type diagnosis when more precise laboratory tests are not available.…”
Section: Intraoral Soft Tissue Involvementmentioning
confidence: 99%
“…In the series reported by Wright, 66.7% of the patients demonstrated generalized, rough, pitted enamel hypoplasia, while the remaining cases showed generalized thinning and/or furrowing of the enamel. 46 Severe forms of JEB have shown a tendency to have thin (≈ 40 μm), prismless enamel. 46,48 While patients with other types of JEB, on the other hand, present a rather thicker but porous enamel with pits.…”
Section: Intraoral Soft Tissue Involvementmentioning
confidence: 99%
“…Eventually, other genetic entities may present ST as dental anomalies: achondroplasia, 65 Ellisvan Creveld syndrome, 2,4 Kreiborg-Pakistani s y n d r o m e , A p e r t s y n d r o m e , 2 C r o u z o n syndrome, 2,66 mucopolysaccharidoses type IV (Morquio syndrome), 67 and type VI (Marateaux-Lamy syndrome), 67,68 Goldenhar syndrome, 69 Noonan syndrome, 70 neurofibromatosis type-1, 71 Ehlers-Danlos syndrome, Hallermann-Streiff syndrome, 2 Nicolaides-Baraitser syndrome, 72 Zimmermann-Laband syndrome, 2 dystrophic epidermolysis bullosa, 73 enamel-renal-gingival syndrome, 74 Fabry disease, 2,4 and non-syndromic cleft lip and palate, 4,75 among others.…”
Section: Other Entities That May Have St Among Their Clinical Findingsmentioning
confidence: 99%